2018
DOI: 10.5713/ajas.17.0654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fermented spent coffee ground on nutrient digestibility and nitrogen utilization in sheep

Abstract: ObjectiveThe objective of the study was to determine the effect of fermented spent coffee ground (FSCG) on nutrient digestibility and nitrogen utilization in sheep.MethodsFermentation of spent coffee ground (SCG) was conducted using Lactobacillus plantrum. Fermentation was performed at moisture content of 70% and temperature of 39°C with anaerobic air tension for 48 h. Four adult rams (initial body weight = 56.8±0.4 kg) were housed in a respiration-metabolism chamber and the treatments were: i) control (Basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…However, observation during the experimental period did not show any rejection of the treatment feed intake by the experimental animals. This in spite of a previous study which found adding wet coffee ground to the experimental feed resulted in the DMI being quadratically decreased in sheep [21], there was also no significant difference between SCG 0% and 10% treatments [8,21]. In this study, as the only 5% of cottonseed was replaced by FSICG in the feed, it was considered that have a small effect on the DMI.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…However, observation during the experimental period did not show any rejection of the treatment feed intake by the experimental animals. This in spite of a previous study which found adding wet coffee ground to the experimental feed resulted in the DMI being quadratically decreased in sheep [21], there was also no significant difference between SCG 0% and 10% treatments [8,21]. In this study, as the only 5% of cottonseed was replaced by FSICG in the feed, it was considered that have a small effect on the DMI.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the result was the opposite to those of feed to milk conversion. In the previous study in sheep, it was reported that as the FSICG level increased in the experimental feed, the gain to feed ratio decreased [8]. The difference between the previous and the current experiment seems to be due to the difference of replacement feed components.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations